Lead point in a colo-colic intussusception identified by combined air and barium enema - Ho-Chuen Chang; Chao-Jan Wang; Jin-Yao Lai (Elsevier, 2018)
We presented a rare case of colo-colic intussusception in a three-year-old girl . By using combined air and barium enema, we successfully identified a colonic polypoid lesion as a lead point before surgery, which was proved a juvenile polyp through pathological confirmation.